In the sense of transcription regulation by G-quadruplexes: asymmetric effects in sense and antisense strands - Agarwal, Tani; Roy, Saumya; Kumar, Santosh; Chakraborty, Tushar Kanti; Maiti, Souvik (Biochemistry, 2014)
G-Quadruplexes occupy important regulatory regions in the genome. DNA G-quadruplexes in the promoter regions and RNA quadruplexes in the UTRs (untranslated regions) have been individually studied and variously implicated at different regulatory levels of gene expression. However, the formation of G-quadruplexes in the sense and antisense strands and their corresponding roles in gene regulation have not been studied in much detail. In the present study, we have elucidated the effect of strand asymmetry in this context. Using biophysical methods, we have demonstrated the formation of stable G-quadruplex structure in vitro using CD and UV melting. Additionally, ITC was employed to demonstrate that a previously reported selective G-quadruplex ligand was able to bind and stabilize the G-quadruplex in the present sequence. Further, we have shown using reporter constructs that although the DNA G-quadruplex in either strand can reduce translation efficiency, transcriptional regulation differs when G-quadruplex is present in the sense or antisense strand. We demonstrate that the G-quadruplex motif in the antisense strand substantially inhibits transcription, while when in the sense strand, it does not affect transcription, although it does ultimately reduce translation. Further, it is also shown that the G-quadruplex stabilizing ligand can enhance this asymmetric transcription regulation as a result of the increased stabilization of the G-quadruplex.